Kebebasan Berkontrak dalam Perjanjian Pinjaman Online dan Implikasinya : Penelitian - Diana Ali Mahmudi; Rita Alfiana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Online loan agreements are executed in the form of electronic contracts that are legally recognized under Articles 1320 and 1338 of the Indonesian Civil Code and Article 1 point 17 of Law No. 11 of 2008 on Electronic Information and Transactions. However, the principle of freedom of contract, which theoretically grants autonomy to the parties, is often not substantively realized because fintech agreements are generally presented as standard form contracts unilaterally drafted by the providers. This imbalance in bargaining power frequently results in unfair clauses prohibited under Article 18 of Law No. 8 of 1999 on Consumer Protection. Moreover, issues such as excessive interest rates, misuse of personal data, and unethical debt collection practices indicate violations of consumer protection and data security regulations as stipulated in the ITE Law, Law No. 27 of 2022 on Personal Data Protection, and Financial Services Authority Regulation (POJK) No. 77/POJK.01/2016. This study employs a normative legal research method using statutory, conceptual, and case approaches to analyze the relationship between the principle of freedom of contract and the civil liability of fintech providers. The findings indicate that fintech operators may be held civilly liable on the basis of breach of contract under Article 1243 of the Civil Code or tort liability under Article 1365 when consumer rights are violated.